3 Archives of Maryland 103 (1642) - (:unkn) unknown (My University, 1642)
All housekeepers to provide an arm, sufficient powder, and ammo for each person able to bear arms. No man able to bear arms shall attend church or chappell or travel any considerable distance from home without an arm and at least one charge of powder and shott.
Keywords: REQUIRED POSSESSION